EMINENSI UMAT MUHAMMAD DALAM SURAH AL-FĪL: Membaca Tafsir Ismail Ascholy dengan Hermeneutika Dilthey - Nazih Hibatullah Muhammad (STAI AL-ANWAR SARANG, 2024)
This article analyzes the significance of the Ummah of Muhammad in Surah al-Fīl through Ismail Ascholy’s commentary in Safīnah Kallā Saya‘lamūn, utilizing Wilhelm Dilthey’s hermeneutical framework as the primary analytical instrument. This study contrasts the prevailing interpretation of Surah al-Fīl, which focuses on divine retribution and the annihilation of Abraha’s forces, by illustrating Ascholy's theological perspective that perceives the event of al-Fīl as an initial indication of divine safeguarding and the elevation of Muhammad's Ummah even before the Prophet's mission commenced. The study reveals that Ascholy’s intellectual and spiritual development within the Nusantara pesantren tradition fosters an interpretive stance that repudiates the generalization of collective punishment following the emergence of prophethood. This attitude is expressed through the selection of relevant Qur’anic verses, the application of the notion of taʿjīl al-ʿadhāb (the hastening of retribution), and the focus on the extraordinary nature of the al-Fīl incident. The stage of Verstehen provides a theological interpretation of Surah al-Fīl as a declarative assertion of the preeminence of the Ummah of Muhammad, rather than simply a historical narrative of divine vengeance. The findings suggest that Ascholy’s exegesis exemplifies a unique style of Nusantara pesantren tafsir, marked by theological optimism and the formation of communal identity, thus broadening the interpretive scope of Surah al-Fīl in modern Qur’anic studies.